The Analysis of Turnover Intention Among Employees at PT Chia Jiann Furniture Indonesia Jepara - Luthfiyatun Nikmah, Luthfiyatun Nikmah; Sumastuti, Efriyani; Setiawati, Ira (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research investigates the influence of work environment factors on the level of turnover intention at PT Chia Jiann Furniture Indonesia Jepara. This research aims to explore the relationship between work environment, workload, burnout, compensation, and job insecurity, with turnover intention in the furniture industry. Quantitative research methods were used using questionnaires to collect data from 218 employee respondents who were selected using probability techniques using simple random sampling. Data were analyzed to examine the relationship between work environment, workload, burnout, compensation, and job insecurity which had a significant influence on turnover intention, while burnout had a statistically lower influence. The results of this study highlight the importance of managing work environmental factors in reducing turnover intention and increasing employee retention in the furniture industry.